I'll Give You the Sun - Nelson, Jandy (New York, New York : Dial Books, an imprint of Penguin Group (USA) LLC, 2014)
"A story of first love, family, loss, and betrayal told from different points in time, and in separate voices, by artists Jude and her twin brother Noah"--
Keywords: Artists -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Gays -- Juvenile fiction; Grief -- Juvenile fiction; Death -- Juvenile fiction; Families -- Juvenile fiction -- California; Artists -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Gays -- Fiction; Grief -- Fiction; Death -- Fiction; Family life -- Fiction -- California; California -- Juvenile fiction; California -- Fiction